Numerical Analysis of Film Cooling Shield Formed by Confined Jet Discharging on a Flat Plate - Al-Hemyari, Mohammed (2019)
The effects of centrifugal force and thermal conductivity on the effectiveness of a film cooling shield are investigated in this study. A confined jet with 90 degree angle is used, to inject cooling fluid into hot steam, to form a film cooling shield that protect a flat plate. Film cooling is modelled in 2D using ANSYS Fluent commercial computation fluid dynamic tool. The RNG k-ε turbulence model with enhanced wall function (EWF) is selected to capture the low-Reynolds number effects near the wall. The selected turbulence model has showed better prediction of the adiabatic film cooling effectiveness accuracy (AFCE) compared to other turbulence models. The results show that centrifugal force alters the flow field and affects the film cooling shield attachment to the flat plate. A clear drop in the AFCE is observed when positive centrifugal force acts perpendicular on the confined jet, which causes overheating in the vicinity of the jet. The effect of wall thermal conductivity on film cooling effectiveness FCE is reported using different thermal conductivity ratios between wall and fluid; mainly, 1,10, 100, 1,000 and 10,000. The results show that thermal conductivity ratios less than 1 have almost no effect on FCE while high thermal conductivity ratios deteriorate the FCE in the vicinity of the jet.